Cell surface receptor kinase FERONIA linked to nutrient sensor TORC1 signaling controls root hair growth at low temperature in Arabidopsis thaliana - Martinez Pacheco, Javier (2022)
Root hairs (RH) are excellent model systems for studying cell size regulation since they elongate several hundred-fold their original size. Their growth is determined both by intrinsic and environmental signals. Although nutrients availability in the soil are key factors for a sustained plant growth, the molecular mechanisms underlying their perception and downstream signaling pathways remains unclear. Here, we identified that a low temperature triggers a strong RH cell elongation response involving the cell surface receptor kinase FERONIA (FER) and nutrient sensor TORC1 pathway. We found that FER is required to perceive limited nutrients availability caused by low temperature, to interacts with and activate TORC1-downstream components to trigger RH growth. Nitrates perceived and transported by NRT1.1 were found to mimic this growth response at low temperature. Our findings reveal a new molecular mechanism by which a central hub composed by FER-TORC1 controls RH cell elongation under low temperature.